Mechanosensory and mechanotransductive processes mediated by ion channels in articular chondrocytes: Potential therapeutic targets for osteoarthritis. Issue 1 (1st January 2021) - Zhang, Kun; Wang, Lifu; Liu, Zhongcheng; Geng, Bin; Teng, Yuanjun; Liu, Xuening; Yi, Qiong; Yu, Dechen; Chen, Xiangyi; Zhao, Dacheng; Xia, Yayi
ABSTRACT: Articular cartilage consists of an extracellular matrix including many proteins as well as embedded chondrocytes. Articular cartilage formation and function are influenced by mechanical forces. Hind limb unloading or simulated microgravity causes articular cartilage loss, suggesting the importance of the healthy mechanical environment in articular cartilage homeostasis and implying a significant role of appropriate mechanical stimulation in articular cartilage degeneration. Mechanosensitive ion channels participate in regulating the metabolism of articular chondrocytes, including matrix protein production and extracellular matrix synthesis. Mechanical stimuli, including fluid shear stress, stretch, compression and cell swelling and decreased mechanical conditions (such as simulated microgravity) can alter the membrane potential and regulate the metabolism of articular chondrocytes via transmembrane ion channel-induced ionic fluxes. This process includes Ca 2+ influx and the resulting mobilization of Ca 2+ that is due to massive released Ca 2+ from stores, intracellular cation efflux and extracellular cation influx. This review brings together published information on mechanosensitive ion channels, such as stretch-activated channels (SACs), voltage-gated Ca 2+ channels (VGCCs), large conductance Ca 2+ -activated K + channels (BKCa channels), Ca 2+ -activated K + channels (SKCa channels), voltage-activated H + channels (VAHCs), acid sensing ion channels (ASICs), transient receptor potential (TRP) family channels, and piezo1/2 channels. Data based on epithelial sodium channels (ENaCs), purinergic receptors and N-methyl-d-aspartate (NMDA) receptors are also included. These channels mediate mechanoelectrical physiological processes essential for converting physical force signals into biological signals. The primary channel-mediated effects and signaling pathways regulated by these mechanosensitive ion channels can influence the progression of osteoarthritis during the mechanosensory and mechanoadaptive process of articular chondrocytes.